Comunicação CAN transmitida por PLC aplicada em veículo de fórmula SAE - Santos, Allison Adones dos [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work proposes and develops an embedded system capable of transmitting a digital communication using the same cable as the electrical supply. The project consists of an electronic board capable of receiving the vehicle's Controller Area Network (CAN) communication. This board adjusts the frequency of the receiving data and passes them down through Power Line Communication (PLC) to a second board, which is able to read and demodulate the original information. In the presented project this information refers to the car's speed, gear and motor rotation. The proposed solutions and components used to develop the project are presented in detail, so that reproductions and improvements are possible. The project was implemented in practice, and its operation and technical feasibility are demonstrated by measurements collected in the project, in addition to measurements, some images of the project in operation are presented. The results obtained support some comments with some proposals for improvements.

Neste trabalho de conclusão de curso foi proposto e implementado um sistema embarcado capaz de estabelecer uma comunicação digital por meio das mesmas vias pela qual o circuito recebe a alimentação elétrica. O projeto consiste em uma placa capaz de receber a comunicação Controller Area Network (CAN) do carro, que modula em frequência os dados recebidos, e os retransmite por Power Line Communication (PLC) para uma segunda placa, que é capaz de interpretar este sinal e restaurar as informações originais. Neste projeto as informações servem para apresentar ao piloto a velocidade do carro, sua marcha atual e a rotação do motor. As soluções propostas e componentes utilizados para desenvolver o projeto, são apresentados detalhadamente, para que seja possível reproduções e aprimoramentos. O projeto foi implementado na prática, e seu funcionamento e viabilidade técnica são mostrados por medições coletadas. Algumas imagens do projeto são apresentadas para ilustrar o funcionamento. Os resultados obtidos embasam algumas sugestões de melhorias que podem ser aplicadas.
CAN communication transmitted by PLC applied to formula SAE vehicle
Keywords: Power line communication; Controller area network; Wire share; Power supply wires with communication; Fórmula SAE; Compartilhamento de fio; Alimentação mais comunicação com dois fios